2021
DOI: 10.1186/s42269-021-00519-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood chemistry of West African dwarf goats fed treated maize cob- and maize husk-based diets with mixture of microorganisms

Abstract: Background Twenty-four West African Dwarf (WAD) goats with average weight of 6.57 ± 0.56 kg were used in investigating the effect of microbial-treated maize cob and husk diets on blood profile. The goats were assigned to six dietary treatments replicated four times in a completely randomized design. Chopped maize cobs and husks were sterilized for 60 min to eliminate any form of contamination and then inoculated with mixture of 15 ml each of Lactobacillus delbrueckii and Neurospora crassa and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…This observation could also be due to the increased need for nutrients by the foetus for rapid growth and development at this stage. This report corroborates with that of Ibhaze et al (2016). The increase in TDMI among goats at a later stage of pregnancy is in agreement with the reports of Rastogi et al (2003) and Shalu et al (1995) who attributed the increase to the changes in the fractional passage rate of digesta from the rumen by a decline in mean retention time of particulate matter as gestation progress.…”
Section: Feed Intake Of Wad Does-fed Experimental Dietssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation could also be due to the increased need for nutrients by the foetus for rapid growth and development at this stage. This report corroborates with that of Ibhaze et al (2016). The increase in TDMI among goats at a later stage of pregnancy is in agreement with the reports of Rastogi et al (2003) and Shalu et al (1995) who attributed the increase to the changes in the fractional passage rate of digesta from the rumen by a decline in mean retention time of particulate matter as gestation progress.…”
Section: Feed Intake Of Wad Does-fed Experimental Dietssupporting
confidence: 92%
“…The crude protein in this study was also higher than the values of 10 and 14% reported by Abdu et al (2012) and Okafor et al (2012) respectively, for optimum goat production. This implied that the diets were adequate to meet the protein requirement of the ruminant and provided effective rumen function (Ibhaze et al, 2016).…”
Section: Chemical Composition Of Dietsmentioning
confidence: 99%
“…However, all blood hematology results in this study were 9–15 × 10 6 /μl, 27–45%, 9–15 g/dl, 4–12 × 10 3 /μl, 28-40fl, 8–12pg and 31–34 g/dl for RBC, PCV, haemoglobin, WBC, MCV, MCH and MCHC respectively, with in the normal physiological ranges reported for clinical healthy sheep ( Jackson and Cockcroft, 2002 ; Radostits et al., 2006 ). The reduction in red blood cell (RBC) counts observed in sheep fed diet containing by-products treated with Trichoderma viride was not below the normal RBC counts reported in healthy sheep, indicated that no haemolytic anaemia and depression of erythrogenesis ( Olafadehan, 2011 ; Ibhaze et al., 2021 ). Packed cell volume (PCV) concentrations below the normal range may indicate anaemia and poor protein quality in the diet ( Radostis et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Packed cell volume (PCV) concentrations below the normal range may indicate anaemia and poor protein quality in the diet ( Radostis et al., 2006 ). Nevertheless, the lower packed cell volume values obtained from the Trichoderma viride treatment by-products fed to the sheep were within the normal physiological range, indicating that the sheep were not anaemic ( Ibhaze et al., 2021 ). Furthermore, the blood haemoglobin concentrations observed in this study were within the normal physiological range, indicate that the sheep had sufficient blood pigment for proper oxygen transport, thus prevent microcytic and hypochromic anaemia caused by iron deficiency ( Olafadehan, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation